Entrepreneurship and Ethics: A Literature Review - Hannafey, Francis T. (Journal of business ethics, 2003)
During the past twenty years, there has been an explosion of new interest in entrepreneurs and their activities. Yet only recently has serious research attention been devoted to the ethical problems encountered by entrepreneurs and their organizations. Entrepreneurs face uniquely complex moral problems related to basic fairness, personnel and customer relationships, distribution dilemmas, and other challenges. This essay surveys contemporary research in entrepreneurial ethics, examines the kinds of ethical dilemmas entrepreneurs confront, identifies major research topics and methodological approaches, and discusses possible directions for future research.